Main reasons for consultation and referral to a stomatologist - Silva, Marceli Moço; Agra , Luara Oliveira; Nascimento , Guilherme Batista do (Journal of Oral Diagnosis, 2025)
Objective: To investigate the main oral lesions diagnosed, the professionals most frequently referring to Stomatology, the time taken to seek care, and the epidemiological profile of the patients. Methods: A census study analyzing all stomatological consultations over a 15-year period. Results: A total of 553 lesions were evaluated across 492 records, with a predominance of white individuals. The most affected sites were the buccal mucosa, gingiva, and lower lip. Most lesions were traumatic in origin, with inflammatory fibrous hyperplasia as the most frequent diagnosis. Malignant lesions accounted for just over 3% and were strongly associated with smoking and occupational sun exposure. Dentists stood out as the main professionals identifying and referring cases. Conclusion: Traumatic lesions remain the most prevalent, but the identification of potentially malignant changes in at-risk groups highlights the need for clinical vigilance and targeted prevention strategies.